1985
DOI: 10.1111/j.1460-2695.1985.tb01202.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Crack Closure and the Extent of the Short Crack Regime in Q1n (Hy80) Steel

Abstract: The paper addresses some aspects of the differences in fatigue crack growth rate behaviour and threshold values obtained for long through-cracks, short through-cracks and surface cracks. Attention is focused on plasticity induced closure in the wake behind the growing crack tip. For long cracks at high La,, closure is found to depend in a linear manner on K,,,, i.e. KO, increases with the size of the monotonic plastic zone. Closure increases at low AK and this is primarily a consequence of the load shedding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 22 publications
4
20
0
1
Order By: Relevance
“…Typical crack lengths associated with small-crack growth behavior range from the order of the material grain size to as large as a millimeter [20][21][22][23]. Such microstructurally small cracks can grow significantly faster than large cracks under the same apparent crack driving force.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Typical crack lengths associated with small-crack growth behavior range from the order of the material grain size to as large as a millimeter [20][21][22][23]. Such microstructurally small cracks can grow significantly faster than large cracks under the same apparent crack driving force.…”
Section: Discussionmentioning
confidence: 97%
“…The ''anomalous'' small crack behavior has been attributed to inapplicability of continuum mechanics assumptions, microstructural interactions, lack of plastic wake effects, and crack-opening mode transients [19][20][21][22][23][24][25][26]. Small cracks have lengths, depths, and plastic zones of a similar size to characteristic microstructural dimensions (typically the grain size) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two sets of results for QIN steel (both calculated from the relative displacement of growth rate curves at 10-t m/cycle). Although James and Knott [ 10] found very little influence of R on the growth rate of long. through cracks in QIN for R between 0.2 and 0.7 (similar to results for QIN in Fig.…”
Section: Quenched and Tempered Steelsmentioning
confidence: 94%
“…As soon as the crack enters into the adjoining grain, CTSD increases abruptly due to the activity of a new coplanar slip in the grain. The growth behavior of a short crack has been referred to as showing a lesser amount of crack closure due to the shorter plastic wake [22]. Shang and Ritchie [23] have observed that the tortuosity of the crack path in duplex structures results in a high level of crack closure near threshold level and is attributed to the sliding displacement.…”
Section: Crack Tip Displacements At the Stage I Short Crack Tipmentioning
confidence: 99%